'A medicine for my state of mind': The Role of Wordsworth in John Stuart Mill's Moral and Psychological Development. Issue 1 (3rd February 2015) - MCKINNELL, LIZ
<x content-type="archive" xml:space="preserve">Abstract</x> According to Jeremy Bentham's account of happiness, pleasure is understood as homogeneous, without qualitative differences between pleasures, and the relation between pleasure and its objects is understood as morally and psychologically arbitrary. John Stuart Mill's 'mental crisis' emerged as he realized the psychological impossibility of living according to this view. His recovery was aided by engagement with the poetry of Wordsworth, through which he developed the notion that the cultivation of character and sentiments is an essential element of a good life. I aim to explore Mill's engagement with Wordsworth, and shed light on how Mill felt able to reconcile hedonic utilitarianism with his new view of the 'inner life' of the individual.